DESIGN AND CONSTRUCTION OF RICE TRESHING MACHINE - Abubakar R. A. (International Journal of Engineering Science Technologies, 2025)
This project presents the design, construction, and experimental testing of a low-cost rice threshing machine aimed at supporting smallholder farmers in rural areas. The machine is built using locally available materials, including mild steel sheets, angle iron, and a 2 HP electric motor. It employs a spike-tooth threshing drum, a vibrating sieve, and a blower system to effectively separate rice grains from panicles and chaff. The main design objectives were to reduce manual labor, minimize post-harvest grain losses, and ensure operational simplicity and affordability. Experimental trials were conducted using 10 kg batches of sun-dried rice panicles over five trials. Performance indicators such as threshed grain weight, unthreshed grain, grain loss, and threshing efficiency were recorded. The machine consistently achieved threshing efficiencies ranging from 85% to 88%, with an average of 86.4%. Grain loss remained constant at approximately 5%, indicating reliable grain separation and minimal breakage. The machine operated smoothly throughout the tests, with stable power transmission, minimal vibration, and no significant mechanical failures. The results demonstrate that the rice threshing machine meets essential design criteria and is suitable for deployment in small-scale farming contexts. The simplicity of the construction allows for easy repair and local fabrication, enhancing its accessibility and sustainability. Recommendations for future improvements include fine-tuning the blower and sieve system and exploring alternative power sources such as solar energy. In conclusion, the rice threshing machine offers a practical and efficient solution for improving post-harvest processing and supporting food security in rice-producing regions.